Insulin resistance is not a risk factor for oesophageal varices development in hepatitis C. (October 2019) - Alsebaey, Ayman; Elhelbawy, Mostafa
Chronic hepatitis C (HCV) patients commonly have insulin resistance which is a risk factor for disease progression. Oesophageal varices may bleed with high mortality. We aimed to assess the relationship between insulin resistance and oesophageal varices. HCV-related compensated liver cirrhosis patients (n = 146) underwent gastroscopy and homeostasis model assessment (HOMA)-IR, HOMA-β and HOMA-S calculations. Their average age was 54.98 years; most (84.9%) patients were men and non-diabetic (60.3%). Patients with oesophageal varices had higher median Model for End-Stage Liver Disease (MELD) scores and comparable Child-Pugh class. Patients with and without oesophageal varices had comparable ( P > 0.05) HOMA scores and insulin resistance percentage of 82.9% versus 85.5%. We therefore conclude that insulin resistance is unrelated to the presence of oesophageal varices.